Menimbang Otoritas Perempuan - Mutamimah, Mutamimah; Miski, Miski (SUHUF, 2024)
This research seeks to explore the participation of women in the dissemination of ‘Ulum Al-Qur’an literature based on the analysis of al-Mu’jam al-Mufahras aw Tajrid Asanid al-Kutub al-Mashhurah wa al-Ajza al-Mansurah by Ibn Hajar al-’Asqalaniy. Women’s acceptance and transmission of Qur’anic sciences literature raises three questions: 1) Who are the women involved? 2) What are the details of their position and involvement? 3) What are the implications of their involvement? In the form of library research and explanatory descriptive analysis, the chosen approach in this study is qualitative. Primary data sources are taken from the book al-Mu’jam al-Mufahras and other literature such as books, mu’jam and masyyakhah books, and scientific articles as secondary data. This study shows that eight women are active, practical, and efficient in researching and narrating 12 ‘ulum Al-Qur’an literature. Thus, a bond is established between the author (the book’s writer) and the compiler (Ibn Hajar al- ’Asqalaniy), bound through these eight women’s intermediaries. Although not equal in quantity, the quality of these women’s involvement has made a contribution that deserves appreciation.